2D fractal analysis of the cutting force and surface profile in turning of iron-based superalloy. (February 2020) - Zhang, Xu; Zheng, Guangming; Cheng, Xiang; Li, Yuan; Li, Li; Liu, Huanbao
Highlights: Cutting force curve and machined surface profile have fractal characteristics. Tool wear can be predicted by the fractal dimension of cutting force curve and machined surface profile. Tool life of coated carbide tool is longer than that of cermet tool. Changing trend of cutting force is consistent with that of tool wear curve. Surface roughness is reduced with the improvement of cutting speed. Abstract: Improving tool life and machined surface integrity was an urgent problem to be solved in turning of iron-based superalloy. Experiments on turning of GH2132 were carried out with the coated carbide tools and cermet tools. The tool life, cutting force and surface roughness were investigated. The fractal characteristics of the cutting force curve and machined surface profile were explored. The tool life of coated carbide tool was longer than that of cermet tool. The results showed that the cutting force curve and machined surface profile had fractal characteristics. The fractal dimension of the cutting force curve was reduced first and then increased with cutting time, and that of machined surface profile was increased with cutting speed, but increased firstly and then reduced with tool wear. The fractal dimension of cutting force curve and machined surface profile was expected to monitor the tool wear and machined surface quality.